PERSEPSI ANGGOTA KPPH TERHADAP PENGELOLAAN TAHURA DI KELURAHAN SUMBER AGUNG KECAMATAN KEMILING KOTA BANDAR LAMPUNG - Risa Agustria Dewinta; Indah Nurmayasari; Suarno Sadar (Lampung University, 2018)
The purposes of this research are to analyze perceptions of KPPH members on Tahura management in Sumber Agung Village and factors related to the perception on Tahura management. This research was conducted in Sumber Agung and respondents were 36 KPPH members of Tahura. Data were collected using a survey method and analyzed descriptively. Rank Spearman correlation test was employed to examine the hypothesis. The results showed the average score of perceptions of most (67%) KPPH members on Tahura management in Sumber Agung Village was 10.12 and categorized as bad. Factor related significantly to KPPH members’ perceptions on Tahura management was knowledge level. Meanwhile, age, education level, social interaction, and income level were not significantly related to KPPH members’ perceptions on Tahura management. Key words: perceptions of KPPH members, Tahura management